Comparative analysis of some commonly consumed allergic food materials - PAUL, MOUMITA; BAG, SUBARNA; DUTTAGUPTA, SOUMILI; Bhattacharya, Malavika (Journal of Drug Delivery and Therapeutics, 2019)
AbstractBackgroundFood allergy is turning out to be one of the vital causes of death in all countries irrespective of the socio-economic status of the people. The extent of mortality from food allergens has increased several folds in the last decade. This has brought research on food allergy and its causative properties to the front. Human beings have the natural power to fight with an allergen, ranging from viruses to food. But in the case of immune-compromise or some other defects in the immune system, individuals can react against some food allergic component(s). Various studies have indicated that cereal or grain particles are more allergic materials than fruits or vegetables. ObjectiveThis study was carried out with the main objective of understanding the variations in various biochemical parameters of a few foods commonly consumed and known to elicit allergic reactions. MethodsIn this study, a few food materials known to elicit allergic reactions in some individuals were selected and comparative analysis (qualitative and quantitative) was performed in an attempt to understand the basis of their differential responses. ResultsThe studies indicated difference in various biochemical parameters and anti-oxidative properties between equivalent quantities of the food samples. ConclusionOur study has revealed differential levels of nutrient contents and anti-oxidative properties between equivalent quantities of the samples of allergic food materials. These findings can be used for further research on the underlying mechanisms of their action.Keywords: Food allergy, Biochemical attributes, Non-communicable diseases, Dietary habits, Nutrition